Multidisciplinary messages on Matooke - Braber, Harmen den; Ven, Gerrie W. van de; Descheemaeker, Katrien K.; Rietveld, Anne M.; Taulya, Godfrey; Kubiriba, Jerome (2021)
On 28-30 September, NARO, IITA, the Alliance of Bioversity International and CIAT and the Plant Productions Systems chair group of Wageningen University and Research organised the ‘Matooke symposium. The aim was to discuss and share our understanding of the sustainability and productivity of banana-based systems in West and South-West Uganda. This report contains a detailed description of the presentations, discussions and key lessons of the symposium. As scientists, we welcome a healthy and critical debate about research findings and their implications. Some topics were indeed critically debated, and as report authors, we tried to do justice to the presentations and discussions. Given the diversity of scientific disciplines and organizations involved in the symposium, the messages in this report do not necessarily reflect the views of the associated organizations.